Standardization in information systems - A. Kimms (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2001)
On a very abstract level, an information system consists of a set of system elements which communicate with each other. Communication is an unproductive operation, so the time needed to communicate data should be kept as short as possible and, to put it in monetary terms, the opportunity costs for communication should be kept small. Now, communicating data is more than just transmitting it, but it consists in large parts of converting data structures that are used by one system element into data structures that are used by another system element. Such conversion can be avoided, if the system elements use a common standard of data structures. Since establishing a standard at a system element incurs standardization costs, a decision maker has to check, if the cost savings gained by standardized communication outweigh the costs for installing the standard. In a recent paper, it is claimed that this so-called standardization problem is an NP-hard optimization problem. We will demonstrate that this is not true, but in fact the standardization problem can be solved in polynomial time by solving a minimum cut problem.
Keywords: 650; Standardization; Enterprise Resource Planning; Client/Server-Architecture; Information System; Network Flow; Minimum Cut; Betriebliches Informationssystem; Bürotechnik; Standardisierung; Mathematische Optimierung; Theorie